The physiological and biomechanical contributions of poling to roller ski skating - Sandbakk, O.; Ettema, G.; Holmberg, H. C. (European Journal of Applied Physiology, 2013)
Poling is considered to make a significant contribution to cross-country skiing with the skating technique. To better understand this contribution, the current investigation compared roller ski skating on a treadmill with the so-called G3 skating technique with (G3-P) and without poling (G3-NP). Seven male elite skiers performed 5-min submaximal tests at 8, 12, and 15 km/h, as well as an incremental test to exhaustion with both techniques on a 5 % incline. Ventilatory variables were assessed by open-circuit indirect calorimetry and three-dimensional kinematics analyzed using the Qualisys Pro Reflex system. G3-P was associated with approximately 15 % higher peak velocity and 10 % higher peak oxygen uptake than G3-NP in the incremental test (both P < 0.01). All ventilatory variables, as well as heart rate and blood lactate concentration were lower with G3-P as compared to G3-NP at 12 and 15 km/h (all P < 0.01). Gross efficiency (i.e., the ratio of work rate to metabolic rate) at 12 km/h was higher in G3-P (14.9 %) than G3-NP (13.5 %) (P < 0.01). Moreover, with G3-P cycle time and length were both 30 % longer, with correspondingly reduced cycle rates (all P < 0.01). In addition, the ski gliding and swing phases were longer and the angle between the skis smaller with G3-P (both P < 0.01), whereas the push-off time was independent of technique and velocity. Taken together, these results indicate that poling makes an important contribution to propulsion and velocity during ski skating, specifically by enhancing peak oxygen uptake, skiing efficiency and associated biomechanical variables.